SocioOntoProcess: a user-centred process for participatory ontology engineering. (2016) - Guergour, Habib-Ellah; Boufaida, Zizette
In this paper, we propose to study how interactions between users can take an active and leading part in the ontology engineering. Our contribution is focused on involving users as co-researchers in the ontology development process in order to bring solutions to the encountered problems. The negligence of user, the sustainability of knowledge and the lack of consensus among different users are mainly the problems facing the ontology engineering. To address these issues, we propose a user-centred process, called SocioOntoProcess, in which we model user interaction by the principles of the social web by exploiting wikis and content sharing to ensure sustainability, availability and sharing knowledge between different users, and using tags and folksonomies to converge towards consensual ontologies.